IMPROVING THE PHYSICAL TRAINING OF FUTURE TEACHERS IN THE CONTEXT OF EDUCATIONAL TRANSFORMATION - Sangirov Nuriddin Iriskulovich (Modern American Journals, 2025)
The transformation of education in the modern era requires the preparation of teachers who are not only professionally competent but also physically well-prepared to meet the challenges of contemporary pedagogy. This article examines the importance of improving the physical training of future teachers in the context of educational transformation, focusing on the integration of innovative approaches and technologies into teacher training programs. The research emphasizes the correlation between physical readiness and professional efficiency, highlighting how enhanced physical capacity supports resilience, stress management, and effective classroom performance. The study also addresses the need to adapt physical education methods in higher pedagogical institutions to meet the demands of rapid digitalization and increasing workloads. By analyzing modern approaches and practical strategies, the article aims to provide a comprehensive understanding of how physical training contributes to the holistic development of teacher candidates and ensures their long-term professional sustainability.
Keywords: Educational transformation, teacher training, physical readiness, professional efficiency, resilience, pedagogical practice, higher education, innovative methods.